Evaluating And Managing The Factors Which Affect The Cohesiveness Of Professional Basketball Teams In Greece - Athanasios, Laios; Laios, Athanasios; Kioumourtzoglou, Efthimis; Panagiotis, Alexopoulos; Nikos, Kostopoulos (European Scientific Journal, ESJ, 2016)
Among the many factors, which can positively or negatively influence the final result of a basketball game and decisively contribute to the achievement of the objectives, is the cohesion between its members. Sport teams characterised by great cohesion, cooperate better, communicate positively and perform more effectively. The purpose of this research was to determine the importance of cohesion, determine the factors that influence it and recommend ways of improving it regarding the part of the coaches of basketball teams. The research was based on the review of literature and field research. The sample was consisted of 24 professional basketball coaches n = (24) from Greece who were coaching in the professional basketball league during 2013-2014 seasons. The research instrument was developed from a relevant review of literature that focused on factors that can influence team cohesiveness. This process leaded to seven variables that can influence basketball team cohesiveness. The basketball coaches were asked to indicate the importance of each variable on seven-point scales ranging from 1, extremely important, to 7, not important at all, by a selfcompleted questionnaire. The results indicated that: a) there are seven factors which can influence the cohesion of a basketball team, b) the «homogeneity» (1.25) considered by the coaches as the most important factor that can influence team cohesiveness and c) the «financial factor» considered as the least important one. Recommendations are suggested for basketball coaches in order to keep a high level of cohesion among their players and contribute to individual and team goals.